Efforts to Improve National Standards in Education Management - Fina Armini (CV. ADIBA AISHA AMIRA, 2022)
The quality of human resources is determined by the quality of their education. Education is a form of human capital investment which if managed properly will have an impact on improving human welfare itself. In Indonesia, the problem of education is very complex. There are 3 aspects of education problems in Indonesia, namely aspects: quality of education, equitable distribution of education and its management. From the aspect of education quality, several important indicators that greatly influence are curriculum, educational content, learning and evaluation processes, teacher quality, educational facilities and infrastructure, and books.